Open and Distance Education to Promote Political Participation in Indonesia - Wulandari, Nisa A'rafiyah Tri; Ningrum, Siti Utami Dewi; Purwantiningsih, Ary (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study empirically evaluated Universitas Terbuka students' political participation. This study used a quantitative approach with a survey research design. Data was collected through the distribution of questionnaires to Sociology Study Program students of the Universitas Terbuka in Malang. The analysis technique utilized descriptive statistics. The study results showed that the average level of student political participation is quite high. Open and distance education had the potential to strengthen the political participation of Indonesian citizens through various activities. Measuring student political participation in universities with an open and long-distance system still needs to be carried out, especially in Indonesia; therefore, the authors recommend that future researchers develop a more credible measurement tool and study it uses a more comprehensive approach.